1994
DOI: 10.1300/j105v18n03_06
|View full text |Cite
|
Sign up to set email alerts
|

Citation Studies in the Humanities and Social Sciences

Abstract: Citation analysis, one form of bibliometrics, is a useful tool for identifying the characteristics of a discipline's literature. Variables commonly studied in a social science analysis often are gender, institutional affiliation, productivity ranking, obsolescence, and format. More uncommon areas are subdisciplinarity and rapidly emerging discrete research fields. Humanities disciplines have not been adequately examined, possibly because research behavior and disciplinary acculturation are not as formalized as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…They found that: "a large part of the publications deal with nationally oriented topics rather than with 'cosmopolitan' topics as in the natural and life sciences; frequent use is made of national language(s) rather than English; an important part of the publication occurs in local outlets rather than in internationally refereed journals; journals are less important than in natural and life sciences; coverage of journals in ISI's Citation Indices is unsatisfactory" (Nederhof et al, 1989, p. 241-42). Hérubel and Buchanan (1994) published a selective and annotated bibliography on citation studies in the humanities and social sciences which covers journal articles, theses, proceedings, book chapters and monographs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that: "a large part of the publications deal with nationally oriented topics rather than with 'cosmopolitan' topics as in the natural and life sciences; frequent use is made of national language(s) rather than English; an important part of the publication occurs in local outlets rather than in internationally refereed journals; journals are less important than in natural and life sciences; coverage of journals in ISI's Citation Indices is unsatisfactory" (Nederhof et al, 1989, p. 241-42). Hérubel and Buchanan (1994) published a selective and annotated bibliography on citation studies in the humanities and social sciences which covers journal articles, theses, proceedings, book chapters and monographs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…4 Herubel and Buchanan highlighted in 1994 both the controversy of bibliometrics applied to the humanities and the opportunities for inquiry into scholarly communication in the humanities that it provides. 5 Although several recent studies have begun to shed light on the overall patterns within the humanities, much remains to be studied. Kellsey and Knievel, authors of two recent citation studies, have offered meaningful comparisons of certain disciplines within the humanities, but have also proclaimed that more studies of individual disciplines are needed to construct a more complete portrait of patterns of scholarly communication within the humanities.…”
mentioning
confidence: 99%
“…(Leydesdorff et al, 2011). In the early decades of bibliometrics, the humanities have been the object of general descriptive citation studies (Hérubel, 1994). More recently, we can find some examples of mapping attempts at a general scale or at the scale of a single discipline or field, which we consider here only if they directly or tangentially discuss history.…”
Section: Mapping the Humanitiesmentioning
confidence: 99%